2022
DOI: 10.1101/2022.07.19.500709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Piks allele of the NLR immune receptor Pik breaks the recognition of AvrPik effectors of the rice blast fungus

Abstract: Arms race co-evolution of plant-pathogen interactions evolved sophisticated recognition mechanisms between host immune receptors and pathogen effectors. Different allelic haplotypes of an immune receptor in host mount distinct recognition against sequence or non-sequence related effectors in pathogens. We report the molecular characterization of the Piks allele of the rice immune receptor Pik against rice blast pathogen, which requires two head-to-head arrayed nucleotide binding site and leucine-rich repeat pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The yeast two-hybrid assay showed that both Piks E229Q -HMA and Piks A261V -HMA as bait bound AVR-PikD as prey to similar levels compared to Pikm-HMA binding with AVR-PikD ( Figs 9A and S18 ). This result is consistent with the result of yeast two-hybrid assay in a recent study [ 117 ]. On the other hand, we found that Piks E229Q -HMA and Piks A261V -HMA as prey weakly bound AVR-PikD as bait, compared to Pikm-HMA binding with AVR-PikD ( Figs 9B and S19 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The yeast two-hybrid assay showed that both Piks E229Q -HMA and Piks A261V -HMA as bait bound AVR-PikD as prey to similar levels compared to Pikm-HMA binding with AVR-PikD ( Figs 9A and S18 ). This result is consistent with the result of yeast two-hybrid assay in a recent study [ 117 ]. On the other hand, we found that Piks E229Q -HMA and Piks A261V -HMA as prey weakly bound AVR-PikD as bait, compared to Pikm-HMA binding with AVR-PikD ( Figs 9B and S19 ).…”
Section: Resultssupporting
confidence: 93%
“…study [117]. On the other hand, we found that Piks E229Q -HMA and Piks A261V -HMA as prey weakly bound AVR-PikD as bait, compared to Pikm-HMA binding with AVR-PikD (Figs 9B and S19).…”
Section: Plos Biologymentioning
confidence: 68%
See 1 more Smart Citation